Invasive intrauterine procedures - Huertas, Erasmo (2015)
Objectives: To determine the frequency and type of intrauterine invasive procedures performed at a unit of fetal medicine and cytogenetic results, immediate complications and indications for chorionic villous sampling and amniocentesis. Design: Observational, retrospective and transversal type study. Setting: Fetal Medicine Unit, Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Pregnant women who accepted an intrauterine invasive procedure. Interventions: Intrauterine invasive procedures in pregnant women were done for various reasons from April 2005 through April 2007. We determined each procedure frequency and compared cytogenetic results, indications and immediate complications of genetic amniocentesis and chorionic villous sampling. Main outcome measures: Characteristics of intrauterine invasive procedures, cytogenetic results and complications. Results: During the 25 months we performed 74 intrauterine invasive procedures, the most frequent being genetic amniocentesis between 15 and 32 weeks (39%) followed by decompressive amniocentesis due to severe polyhydramnios (24%). Chorionic villous sampling was the third type of procedure done and resulted usually in euploid fetuses (53,3%), similar to genetic amniocentesis (62,1%). Main indication for chorionic villous sampling and genetic amniocentesis was the presence of congenital malformations by ultrasound markers (frequency respectively 80 and 86%). Genetic amniocentesis detected up to 27,5% of chromosomopathies compared with only 6,7% with chorionic villous sampling. There were no immediate complications (66,7% with chorionic villous sampling and 89,7% with genetic amniocentesis). Conclusions: Our Unit of Fetal Medicine becomes the main public sector institution to perform intrauterine invasive procedures in the country, both for diagnostic and therapeutic reasons, 3 procedures per month. Amniocentesis leads with 53% of frequency, without complications in the first 72 hours following the procedure.